Costal cartilages - a clue for determination of sex - Rejtarová, Olga; Slížová, Dáša; Šmoranc, Pavel; Rejtar, Pavel; Bukač, Josef (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2004)
Mineralization and ossification in the human costal cartilages were studied radiologically. The aim of our study was to evaluate differences between males and females with respect to patterns of costal cartilage calcification and also with respect to ageing. Material for this study consists of 1044 chest and abdominal radiograms of the Czech population from the Department of Radiology (537 males and 507 females). Further radiograms of 18 chest plates were obtained at routine necropsy of cadavers. The radiograms were examined for pattern of ossification of the costal cartilage. The first rib cartilages were not considered because there are no sex differences. The lower ribs exhibit sexual dimorphism. Mineralization and ossification changes appear at the end of puberty and their occurrence increases with age. The sexual difference in pattern of human costal cartilages is statistically significant and thus highly predictive of sex determination.
Keywords: Adolescent; senioři; Male; Female; dítě; Aged; Middle Aged; Sex Characteristics; chrupavka; mužské pohlaví; ženské pohlaví; Adult; Cartilage; Child; Calcification, Physiologic; senioři nad 80 let; mladiství; dospělí; lidé středního věku; žebra; Ribs; Aged, 80 and over; lidé; fyziologická kalcifikace; Humans; pohlavní dimorfismus